2010
DOI: 10.1111/j.1747-0803.2009.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Progression of Coronary Aneurysms, a Case of Delayed Onset Kawasaki Disease as Depicted by Cardiac Computed Tomography Angiography

Abstract: Without prompt therapy, fever and manifestations of acute inflammation can last for several weeks to months with increased risk toward complications. The incidence of coronary artery aneurysms has been noted to be 25% in untreated patients with a mortality rate of up to 2%. Using low-dose protocols along with high spatial and temporal resolution of cardiac CT angiography may provide a useful and complimentary imaging modality in accurate diagnosis and follow-up of patients with KD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…So far, KD is diagnosed based primarily on the clinical features; there are no specific laboratory tests for the early identification and diagnosis 4 . However, delay accurate diagnosis may cause increased mortality and morbidity from complications of KD 5 . Previous studies indicated that thrombocytosis is common in the subacute stage of KD patients 68 .…”
Section: Introductionmentioning
confidence: 99%
“…So far, KD is diagnosed based primarily on the clinical features; there are no specific laboratory tests for the early identification and diagnosis 4 . However, delay accurate diagnosis may cause increased mortality and morbidity from complications of KD 5 . Previous studies indicated that thrombocytosis is common in the subacute stage of KD patients 68 .…”
Section: Introductionmentioning
confidence: 99%
“…It is mostly used in both acute and chronic phases of KD. Newer generation computed tomographic (CT) scanners provide detailed information on the arterial location, size, structure, and number of CAAs with improved spatial resolution and better image quality [ 2 , 12 , 13 ]. As per the technical advancements in imaging, the radiation dose used was significantly lower for imaging with a 256-slice CT scanner at a heart rate (HR) of 132 bpm.…”
Section: Discussionmentioning
confidence: 99%
“…However, treating refractory KD with IVMP should be undertaken with caution because of adverse effects 12). Steroid treatment has also been associated with the development of CAA or rupture in many case reports 13)14)15)16). A recent study shows that IVIG-resistant patients with alternative corticosteroid therapy more frequently develop coronary artery lesion (CAL) than those without corticosteroid therapy 17).…”
Section: Discussionmentioning
confidence: 99%